Correlation between TPACK and Conation of Certified Biology Teachers in State High Schools in Banda Aceh - Risma Rahmawati Fhonna; Andi Ulfa Tenri Pada; Cut Nurmaliah; Safrida; Ismul Huda (Jurnal Penelitian Pendidikan IPA, 2025)
The ability to apply TPACK will make it easier for teachers to teach material to students. One of the factors that influences TPACK in teachers is conation. If a teacher has a connection, TPACK can run well. This research aims to determine the relationship between TPACK and the certification of Biology teachers at State High Schools in Banda Aceh. The approach used in this research is to use a quantitative approach while the type of research is correlational research. The subjects used in this research were all Biology teachers who had been certified at the high school level in Banda Aceh. The data analysis technique used in this research is qualitative data and quantitative data. Qualitative data was obtained from interviews and observations, while quantitative data was obtained from questionnaires filled in by respondents and then data analysis was carried out using SPSS. The results of the research show that the calculated rvalue for the relationship between TPACK and conation is 0.538 > rtable 0.316, so it can be concluded that there is a medium category relationship between the TPACK variable and the conation variable. Because the calculated r in this analysis is positive, it means that the relationship between the two variables is positive.